MENGGALI KONSEP FILOSOFIS MBARU GENDANG SEBAGAI SIMBOL IDENTITAS DAN PUSAT KEBUDAYAAN MASYARAKAT MANGGARAI, FLORES, NUSA TENGGARA TIMUR - Mathias Adon (Jurnal Masyarakat dan Budaya, 2025)
This study focuses on efforts to understand the philosophical concept of the mbaru gendang as a symbol of identity and the center of Manggarai culture. This study aims to explore the values of local wisdom contained in the symbols, forms, and functions of the mbaru gendang. This research is motivated by an awareness of the wisdom values contained in the form and structure of the new Manggarai drum culture so that it can be used as beautiful philosophical thoughts for Indonesian philosophy that is sustainable throughout time. The method used is observation and literature study. This study found that the symbols and shapes of the mbaru gendang have very high cultural philosophical values. So this research contributes to the exploration of the wealth of wisdom of the mbaru gendang so that it becomes a philosophical presentation that can be actualized in the daily life of the Indonesian people. Besides that, this research is an attempt to promote the mbaru gendang as a symbol of identity and cultural center of the Manggarai community.